If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x = -2x + -6 Reorder the terms: -5x = -6 + -2x Solving -5x = -6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -5x + 2x = -6 + -2x + 2x Combine like terms: -5x + 2x = -3x -3x = -6 + -2x + 2x Combine like terms: -2x + 2x = 0 -3x = -6 + 0 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| 7500x=5900x+88000 | | (x+72)(x+48)=6912 | | -15-32n=4(-8n+4) | | 120-5a+7=8a-16a-35 | | 8y+1=9y-7 | | 4x+89=7x-74 | | 3x+2=3x-3 | | 4h^2=-62h-30 | | 2x/3=15 | | 2x/3-9=32 | | (7x^2-3x-16)+(8x^2+8x)= | | 240x+35=5y+135x | | 3x^3=81 | | 6y=z | | 3(3e+2f)+yf+2=0 | | Y=5/2x+1 | | 4x+3x+5= | | 24+b=40 | | 38-y=250 | | 18+4y=2(3-y) | | c=P+3b+a | | 5/(b+5)-2/b | | 23x^2-15=6x | | 4/x=8/17 | | 9+4y=(3-y) | | -3(x+5)=2x+5 | | -4+5x=14-3x | | F(x)=2x-5 | | -18/-3 | | 34y+9=3(12y-18) | | 18x^3-9x^2-2x+1=0 | | 3+0.5x=4 |